Wakaf According to The Quran and its Transformations in Indonesia's Contemporary Era - Zuhri, Ahmad; Yumni, Aufah (Fakultas Syariah INSURI Ponorogo, 2023)
Objective: This article aims to reveal the meaning of waqf according to the Koran and its transformation in the contemporary era in Indonesia. Method: This research method uses Library Research whose primary focus is on library books and other literature. Based on the research objectives, it includes basic research, i.e. research to broaden and deepen theoretical knowledge. Result: This digital transformation is described as the total and overall effect of digitalization on society. Khan said that digitization has enabled the digitization process, which drives stronger opportunities to transform and change existing business capital, socio-economic structures, legal and policy measures, organizational patterns, cultural barriers, etc.